Isolation and Antifouling Activity of Azulene Derivatives from the Antarctic Gorgonian Acanthogorgia laxa - Patiño Cano, Laura Patricia (2018)
Three azulenoid sesquiterpenes (1 – 3) were isolated from the Antarctic gorgonian Acanthogorgia laxa collected by bottom trawls at −343 m. Besides linderazulene (1), and the known ketolactone 2, a new brominated C16 linderazulene derivative (3) was also identified. This compound has an extra carbon atom at C(7) of the linderazulene framework. The antifouling activity of compounds 1 and 2 was assayed in the laboratory with Artemia salina larvae, and also in field tests, by incorporation in soluble-matrix experimental antifouling paints. The results obtained after a 45 days field trial of the paints, showed that compounds 1 and 2 displayed good antifouling potencies against a wide array of organisms. Compound 3, a benzylic bromide, was unstable and for this reason was not submitted to bioassays. Two known cembranolides: pukalide and epoxypukalide, were also identified as minor components of the extract.